Influence of clustering round magnetic nano-dots on magnetization reversal - Blachowicz, T; Ehrmann, Andrea
Square and round magnetic nano-dots of varying dimensions exhibit a large amount of possible magnetization reversal processes, from domain wall nucleation and propagation to multi-vortex states. Clustering such single nano-dots, however, may strongly modify these magnetization reversal processes due to the interactions between neighboring particles. Here we thus investigate the difference between magnetization reversal processes in clusters of hexagonally arranged round nano-dots under different orientations of the external magnetic field in comparison with single particle behavior.